PROJECT DESIGN OF LEARNING ACTIVITY CYCLE FROM THE PERSPECTIVE OF ACTIVITY AND COMPETENCE APPROACH - E. O. Pokhomchikova (Moscow Polytechnic University, 2018)
The article presents a project of attendance-based and distance learning activity cycle within a discipline. This cycle is based on the activity and competence approach, which lies at the heart of the Federal state educational standards of the third generation. The article adduces the basic principles of this approach, namely: the recognition of learning as a pedagogical and educational activity, where the leading role is assigned to learning activity - active self-directed students' activity aimed at the development of their own competence; practical orientation; the expression of learning outcomes in the ability to successfully operate in various situations, including the professional sphere. The project provides a rationale for choosing a topic that reflects the core competence towards which the educational process is directed. The chosen topic is module involving the complete cycle of competence development including stages "Know", "Able to", "Master" and "Be". While studying of the topic the model of blended (attendance-based and distance) learning can be implemented. Input, intermediate and final educational objectives are described in terms of competence development stages. The article presents and describes in detail the cycle of educational activities for achieving the set goals-results. This cycle, which can be viewed as a scale illustrating the competence development, includes four levels: 1) informational (acquisition of data and knowledge), 2) activities (development of special skills), 3) creativity (development of general abilities and skills), and 4) value and sense (development of personal value system). The conception of developing education implies implementation of a complex of organizational forms of interaction between a teacher and trainees such as lections, seminars (webinars), practical training, self-directed work, presentations, online and offline forums, conferences (videoconferences), tutorials, master classes, consultations, project sessions, trainings, and Sunday schools. The training assignments correspond to the four levels of competence development and include such types as current, interim, key, and the final. The achievement of the learning outcome - professional competence is accomplished by the progression movement along the built target framework.